2017
DOI: 10.15405/epsbs.2017.12.02.20
|View full text |Cite
|
Sign up to set email alerts
|

The Search For Understanding Organizational Resilience

Abstract: Organizations' ability to cope with environmental uncertainties, threats, crises, and unexpected events depends on their resilience capacity. Resilience is to survive after a hard and distressful event. The concept, which is a research topic in a wide range of disciplines, has begun to be scrutinized recently in organizational science and the literature in this area is still in the developmental stage. This also indicates the need for studies on organizational resilience. The studies to be done in this area wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
7
0
4
Order By: Relevance
“…Nevertheless, the proactive resilience strategy seems to be more promising for enhancing organisational resilience regarding the influence of trends on their BM. Ince (2017) reported that highly resilient organisations are characterized by an effective coping of change, threats or challenges; quick adaption to disruptions; and fast recovery to equilibrium after a destructive event. Further, they highlight several actions and reflexes of resilient organisations, including the critical aspects of planning and preparation, sensemaking, response and recovery and rapidity (Ince, 2017).…”
Section: Ijis 125mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the proactive resilience strategy seems to be more promising for enhancing organisational resilience regarding the influence of trends on their BM. Ince (2017) reported that highly resilient organisations are characterized by an effective coping of change, threats or challenges; quick adaption to disruptions; and fast recovery to equilibrium after a destructive event. Further, they highlight several actions and reflexes of resilient organisations, including the critical aspects of planning and preparation, sensemaking, response and recovery and rapidity (Ince, 2017).…”
Section: Ijis 125mentioning
confidence: 99%
“…Ince (2017) reported that highly resilient organisations are characterized by an effective coping of change, threats or challenges; quick adaption to disruptions; and fast recovery to equilibrium after a destructive event. Further, they highlight several actions and reflexes of resilient organisations, including the critical aspects of planning and preparation, sensemaking, response and recovery and rapidity (Ince, 2017). Moreover, this study finds that within the proactive resilience strategy, the usage of foresight methods was mentioned most often by experts.…”
Section: Ijis 125mentioning
confidence: 99%
“…Num contexto generalista, Ince et al (2017) afirmam que a resiliência organizacional surge quando as empresas são obrigadas a manter suas habilidades, competências e capacidades organizacionais em um ambiente em mudança, desafiando situações de competição.…”
Section: Resiliência Organizacionalunclassified
“…Boin; Comfort; Demchak 2010Capacidade de "salto para trás" em caso de uma perturbação. Mafabi;munene;ntayi (2012) Capacidade de uma organização para ser proativo e / ou reativo para lidar com as demandas ambientais e ameaças Ince et al (2017) Capacidade das organizações para lidar com incertezas ambientais, ameaças, crises e acontecimentos inesperados Wieland;Marcus Wallenburg (2013) Capacidade de investir na rotina de compartilhar conhecimento sobre mudanças relevantes no ambiente, em avançar ou quando ocorrerem. Manab;aziz (2019) Capacidade de uma organização antecipar e planejar com antecedência para lidar com eventos potenciais inesperados por meio da abordagem SRM para a sobrevivência da empresa a longo prazo.…”
Section: Resiliência Organizacionalunclassified
See 1 more Smart Citation